1998
DOI: 10.1016/s0032-9592(98)80060-5
|View full text |Cite
|
Sign up to set email alerts
|

On-line monitoring of citric acid production in solid-state culture by respirometry

Abstract: The aim of this work was to study the possibility of monitoring citric acid production from mussel processing wastes (MPW) by Aspergillus niger in solid-state culture (SSC) on an inert support. This was conducted by measuring CO 2 and O 2 concentration in exhaust gases, using an automatic sampler connected to a gas chromatograph and a data acquisition system. The procedure permitted information on the physiological state of the culture to be obtained. A relationship between citric acid accumulation and a decre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 18 publications
0
4
0
1
Order By: Relevance
“…Oxygen level is an important parameter for citric acid fermentation. Several researchers (Pintado, Lonsane, Gaime-Perraud, & Roussos, 1998;Prado et al, 2004) have studied the influence of forced aeration on citric acid production and the metabolic activity of A. niger in SSF by respirometric analysis. They showed that citric acid production was favoured by a limited biomass production, which occurred with low aeration rates.…”
Section: Citric Acidmentioning
confidence: 99%
“…Oxygen level is an important parameter for citric acid fermentation. Several researchers (Pintado, Lonsane, Gaime-Perraud, & Roussos, 1998;Prado et al, 2004) have studied the influence of forced aeration on citric acid production and the metabolic activity of A. niger in SSF by respirometric analysis. They showed that citric acid production was favoured by a limited biomass production, which occurred with low aeration rates.…”
Section: Citric Acidmentioning
confidence: 99%
“…Solid-state fermentation Figure 3(a) shows the CO 2 production rate. The generation of CO 2 is usually detected when spore germination is active, 28 which occurs after 10 h in the SSF process for Aspergillus sp. In this study, the daily CO 2 production rate increased from day 1 to day 7 of SSF, reaching a maximum value of 17.35 ± 0.216 g kg −1 day −1 , and maintenance stabilized after day 8.…”
Section: Determination Of the Optimal Operating Conditions Of Tpc Ext...mentioning
confidence: 99%
“…There is great interest in the production of citric acid via SSF by fungi, numerous research has studied the microbial production of citric acid by fungi by using both solid-state and submerged state fermentation. Many fungi species could be involved in citric acid production, although most research showed that the species of Aspergillus are the most capable of producing citric acid such as A. niger (Hang & Woodams 1986); Roukas and Kotzckidou 2020; Pintado et al, 1998 andLu et al 1997); A. aculeatus (El Dein & Emaish 1979); A. awamori (Grewal & Kalra, 1995); A. wentii (Karow & Waksman, 1947); and A. foetidus (Chen 1994 andTran et al, 1998). Also, Grewal & Kalra, 1995, reported that it could be use Penicillium janthinelum in citric acid production.…”
Section: Isolation Of Citric Acid Producing Fungimentioning
confidence: 99%